Enhancing e-learning effectivity through the discussion method combined with e-portfolio assignments for vocational education master students during a pandemic - Muchlas Muchlas (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2020)
Discussion is one of the effective methods to make the e-learning condition to be student-centered. However, the use of the discussion method only focuses on specific issues, so that it could not explore broader knowledge and obtain feedback from many sources. The study aims to get the impact of using the discussion method combined with e-portfolio assignments on e-learning during the Covid-19 pandemic in students' perceptions perspective. This research has been carried out with a simple procedure using a survey approach. The research subjects are students of the Vocational Education Master Degree who participated in the Vocational Learning Theory and Strategy course. The research instrument is a closed questionnaire to explore student perceptions, including 8-aspects, using statements with options on a 4-degree Likert scale. The average perception level for each aspect is the total score divide by the total maximum score of the research subjects. Perception is declared good if the ratio is above 80%. The results showed that e-portfolio assignments combined with the discussion method in e-learning gave positive student perceptions. Students feel that an e-portfolio is a learning tool that can increase learning effectiveness, provide useful feedback, help carry out self-assessments, and increase interaction between teacher and student. The results also show that the students gave a positive perception to the e-portfolio as a tool that is easy to use, useful, systematic, motivating, and effectively to improve learning outcomes. In general, this result shows that e-portfolio tools can increase the effectiveness of e-learning.